1990
DOI: 10.1007/bf00008187
|View full text |Cite
|
Sign up to set email alerts
|

Impact of intensive cage fish farming on the phytoplankton and periphyton of a Scottish freshwater loch

Abstract: Nutrients, phytoplankton and periphyton were monitored in a 71 ha shallow, unstratified lake used for intensive cage culture of rainbow trout. Inorganic nitrogen, ortho-phosphate and suspended solids were significantly higher near the cages and the bottom and, although declining during summer, nutrients did not reach levels which limit phytoplankton growth. Microcystis aeruginosa dominated the phytoplankton, with surface chlorophyll a reaching 189 g 1-in August, but with no subsequent bloom collapse or deoxyge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
12
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 39 publications
(47 reference statements)
4
12
0
Order By: Relevance
“…Cornel and Whoriskey (1993) reported that cage culture of rainbow trout (Oncorhynchus mykiss) in Quebec had short-term, localized impacts on the lake environment. Similar results were reported by Stirling and Dey (1990). In the present study, the gross yield of fish in 2000 was not high (16.0 MT in total), but the nutrient loads from the diets used were prominent.…”
Section: Discussionsupporting
confidence: 91%
“…Cornel and Whoriskey (1993) reported that cage culture of rainbow trout (Oncorhynchus mykiss) in Quebec had short-term, localized impacts on the lake environment. Similar results were reported by Stirling and Dey (1990). In the present study, the gross yield of fish in 2000 was not high (16.0 MT in total), but the nutrient loads from the diets used were prominent.…”
Section: Discussionsupporting
confidence: 91%
“…This proportion is higher than that from other cultures such as salmon farming where feed wastage is below 5 %. Nutrient losses reported in the present study were similar to those described in previous publications, where losses were generally attributed to management practices, feed quality, and fish metabolism (Stirling and Dey 1990;Foy and Rosell 1991;Cornel and Whoriskey 1993;Halver and Hardy 2002;Abery et al 2005;Islam 2005). The stable isotope data and SIAR model indicated that the fish biomass was an important fate of feed.…”
Section: Discussionsupporting
confidence: 88%
“…Many studies have been conducted on the effects of cage systems on water quality, suspended matter, bottom sediment, plankton, periphyton, and benthic communities. The results were highly variable from system operating causing no changes on the lake conditions (Hakanson et al 1998;Costello et al 2004); to others producing short-term and localized effects (Cornel and Whoriskey 1993); or still other systems significantly impacting water quality, sedimentation rates, and phytoplankton and benthic communities (Stirling and Dey 1990;An and Kim 2003;Guo and Li 2003;Figueredo and Giane 2005;Alves and Baccarin 2006;Tavares et al 2010).…”
Section: Introductionmentioning
confidence: 97%
“…In another study carried out in a rainbow trout farming enterprise, it was found that pH and dissolved oxygen amounts did not significantly vary between the stations, while nutrient elements (N, P) (excluding nitrite nitrogen) were found to be higher in cage stations similar to the findings above (Demir et al, 2001). Similarly, other researchers reported that there was no difference between the enterprise and reference stations in terms of nitrite nitrogen and nitrate nitrogen (Stirling and Dey, 1990). Interestingly, Cornel and Whoriskey (1993) reported that in enterprises that make production below their capacity, N and P levels can be the same in the enterprise and reference stations. )…”
Section: Resultsmentioning
confidence: 96%
“…Researches have shown that negative effects vary according to enterprise capacity, currents, change ratio and total volume of water and the technology used in fish farming Stirling and Dey, 1990;Pitta et al, 1999). The most common effects were reported to be decreased dissolved oxygen, pH values and sechi depth, and increase of suspended solid matter, nutrient, electrical conductivity and chlorophyll a (Rast and Holland, 1988;Weglenska et al 1987;Beveridge 1984.…”
Section: Resultsmentioning
confidence: 99%